1997
DOI: 10.1068/p261059
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Patterns Made during Brief Examination of Two-Dimensional Images

Abstract: Measurements were carried out of saccadic eye movements made during brief (3 s) examination of images which the observer was asked to identify. Each image was identified in three forms: low-pass filtered, high-pass filtered, and unfiltered. The analysis of the eye-movement patterns was based on the locations of fixations made during examination of the images, for which purpose a least-squares measures of similarity between two sets of locations was introduced. It is shown that there is a high degree of similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 23 publications
4
83
0
Order By: Relevance
“…Using a different definition of the feature, Reinagel and Zador (1999) also reported this correlative effect between luminance contrast and human overt attention. Their result was later confirmed in several other studies (e.g., Krieger, Rentschler, Hauske, Schill, & Zetzsche, 2000;Parkhurst & Niebur, 2003), although under some presentation conditions a dependence on spatial frequency may obstruct the effect for unfiltered stimuli (Mannan, Ruddock, & Wooding, 1997;Tatler, Baddeley, & Gilchrist, 2005). Recently, a study in our laboratory also replicated the correlation of luminance contrast to human fixation, but we demonstrated that this effect of luminance contrast is not causal (Einhäuser & König, 2003).…”
supporting
confidence: 85%
“…Using a different definition of the feature, Reinagel and Zador (1999) also reported this correlative effect between luminance contrast and human overt attention. Their result was later confirmed in several other studies (e.g., Krieger, Rentschler, Hauske, Schill, & Zetzsche, 2000;Parkhurst & Niebur, 2003), although under some presentation conditions a dependence on spatial frequency may obstruct the effect for unfiltered stimuli (Mannan, Ruddock, & Wooding, 1997;Tatler, Baddeley, & Gilchrist, 2005). Recently, a study in our laboratory also replicated the correlation of luminance contrast to human fixation, but we demonstrated that this effect of luminance contrast is not causal (Einhäuser & König, 2003).…”
supporting
confidence: 85%
“…Although the results of Experiment 1 suggested that eye movement consistency is related to scene recognition, it remains unclear to what extent this consistency could be attributed to episodic memory or idiosyncratic scene preferences consistent across scene repetitions (Mannan, Ruddock, & Wooding, 1997). Specifically, a participant might be inclined to direct his gaze toward for example, flowers in every picture, and hence increase the amount of fixations were analyzed (i.e., fixations number 2-4).…”
Section: Methodsmentioning
confidence: 98%
“…Furthermore, landing position influenced fixation time: The duration of the first fixation on an object decreased and the probability of refixating an object increased as the deviation of the initial landing position from the center of the object increased. Mannen et al (1995Mannen et al ( , 1996Mannen et al ( , 1997 had viewers look at normal scenes or the scenes after they had been either high-pass or low-pass filtered. They found that viewers looked in pretty much the same locations across the three versions of the scene.…”
Section: Eye Movement Controlmentioning
confidence: 99%